Molecular and Functional Analysis of the Pixb Gene in Xenorhabdus Nematophila - (:unkn) unknown (My University, 2016)
Xenorhabdus nematophila and the entomopathogenic nematode Steinernema carpocapsae form a mutualistic relationship facilitating the infection, death and consumption of an insect host. The infective juvenile (IJ) form of S. carpocapsae invades the insect host through natural openings and proceeds to the hemocoel where exposure to hemolymph stimulates the release of X. nematophila from the anterior vesicle. Excreted X. nematophila releases immunosuppressive compounds and insect toxins into the insect hemolymph that facilitates death of the host. As X. nematophila reaches high cell density it secretes exoenzymes that degrade insect tissues and produces antibiotics that reduce microbial competition. S. carpocapsae utilizes the insect remains as a nutrient source and reproductive site. When grown in nutrient-rich laboratory broth X. nematophila produces two distinct crystalline inclusion bodies. One crystalline inclusion is composed of the methionine-rich PixA protein. The other inclusion body is composed of IP2 (PixB), a 22 kDa protein that is not methionine-rich. While the pixA gene had been studied previously the pixB gene had not been identified. To better understand the function of PixB, the pixB gene was identified and its expression was analyzed by GFP promoter reporter constructs in cells grown under biologically relevant conditions. In addition, comparative genomic and phylogenetic analyses were conducted to assess the prevalence and distribution of pixB in other microbial species. A pixA-minus strain of X. nematophila grown in LB broth produced crystalline inclusion bodies as visualized by transmission electron microscopy. In contrast, inclusion bodies were rarely detected in cells grown in insect cell culture medium (Grace’s medium) that mimics insect hemolymph. Furthermore, inclusion bodies were not present when bacteria were grown directly in the insect host. These findings indicate that crystalline inclusions form when X. nematophila grows in nutrient-rich medium but not under more biologically relevant conditions. The pixB gene was found to possess highly conserved σ70 promoter consensus sequences while the promoter of pixA was less well conserved. Expression analysis in Grace’s insect medium revealed that initial expression of pixB occurred during late log phase growth while pixA was activated during mid log phase. Unexpectedly, pixB was expressed at 2.8-fold higher levels in Grace’s insect medium than in LB broth. The reason that inclusion bodies form in LB broth even though the apparent expression of pixB is lower than in cells grown in Grace’s medium is not presently understood. Consistent with results in Grace’s medium the expression of pixB was higher than pixA in cells grown for 48 hours in the insect host. The pixB gene was found to be flanked by mobile genetic elements and present in only 3 of 18 sequenced Xenorhabdus genomes and was widespread in different classes in proteobacteria. Sequence comparison of the PixB-type proteins revealed two regions of sequence conservation (CD1 and CD2) separated by a linker region of similar length in all proteins. Phylogenetic analysis indicated that pixA and pixB belonged to the same clade and provided evidence of extensive horizontal gene transfer of the pixB gene. In addition, another Pix-type protein group was identified in gammaproteobacteria that possessed glycine-rich regions. We refer to this group as the PixC-type proteins. Together, these findings represent a new family of genes that had not been previously recognized.
Keywords: Aida; Inclusion Body; Pixa; Pixb; Pixc; Xenorhabdus